Transformation Of Information Technology Capacity As A Marketing Media Of The "Lontar Sewu" Tourism Village, Hendrosari Village, Gresik Regency - Sukaris Sukaris; Budiyono Prestyadi; Al kusani (Kontribusia : Research Dissemination for Community Development, 2020)
Problems that occur in partner tourism villages are that village tourism is still managed and marketed improperly so that it is less marketable that relies on conventional marketing with marketing knowledge resources that are still not optimal, the main problems are marketing management knowledge, marketing personnel, and mastery of marketing support technology. The purpose of this activity is to transform the capacity of information technology as a marketing media for tourism villages specifically, first; by strengthening institutional capacity and human resources (training and mentoring), secondly; strengthen digital marketing of tourist villages. Methods of implementing activities through Focus Group Discussion (FGD) with POKDARWIS; the second phase is strengthening the institutional capacity of BUMDES and POKDARWIS. The result of the activity is that the BUMDES and POKDARWIS managers have been able to transform the 3-P strategy which includes segmenting targeting and positioning. Managers must be able to combine and internalize the 3-P strategy into digital marketing strategies. Suggestions for managers are first; managers must update the capacity on mastering the latest marketing technology so that they can keep up with the changing tastes of visitors' tastes. Service must be the package of activities so that the strategy to improve service quality becomes an inseparable part of all marketing efforts both conventional and digital.